PREDICTORS OF TREATMENT RESISTANCE IN ANKYLOSING SPONDYLITIS - Kedyk, I.O.; Stanislavchuk, M.A.; Kuzminova, N.V.; Lozinsky, S.E.; Kniazkova, I.I.; Shapoval, I.I.; Shalkovskyi, Y.I. (World of Medicine and Biology, 2025)
The study aimed to determine the predictors of treatment resistance in patients with ankylosing spondylitis with a neuropathic component of pain syndrome. We examined 142 patients who were diagnosed with ankylosing spondylitis according to the modified New York criteria. Among the examined patients, 113 (79.6 %) were men, and 29 (20.4 %) were women; the average age was 42±8.8 years, and the duration of the disease was 6.8±3.5 years. The control group consisted of 25 practically healthy individuals (19 men and 6 women) of the same age. It was found that in patients with ankylosing spondylitis with the presence of a neuropathic component of pain syndrome, the level of glial neurotrophic factor (GDNF) was significantly (p